DAS181 treatment of hematopoietic stem cell transplant patients with parainfluenza virus lung disease requiring mechanical ventilation. Issue 1 (3rd January 2014) - Chalkias, S.; Mackenzie, M.R.; Gay, C.; Dooley, C.; Marty, F.M.; Moss, R.B.; Li, T.; Routh, R.L.; Walsh, S.R.; Tan, C.S.
Abstract Parainfluenza infection is a cause of significant morbidity and mortality in allogeneic hematopoietic stem cell transplant (HSCT) patients. DAS181 is a novel antiviral agent with activity against influenza and parainfluenza. We report the first 2 cases, to our knowledge, of successful DAS181 use in ventilated HSCT patients with severe parainfluenza lung disease.